The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1016/j.neuron.2008.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ablation of V2a Ipsilateral Interneurons Disrupts Left-Right Locomotor Coordination in Mammalian Spinal Cord

Abstract: The initiation and coordination of activity in limb muscles are the main functions of neural circuits that control locomotion. Commissural neurons connect locomotor circuits on the two sides of the spinal cord, and represent the known neural substrate for left-right coordination. Here we demonstrate that a group of ipsilateral interneurons, V2a interneurons, plays an essential role in the control of left-right alternation. In the absence of V2a interneurons, the spinal cord fails to exhibit consistent left-rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
409
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 314 publications
(433 citation statements)
references
References 57 publications
20
409
3
1
Order By: Relevance
“…A consecutive study confirmed these findings and showed that the disruption in left-right alternation was most pronounced at intermediate locomotor frequencies (Crone et al, 2009). Together, these studies therefore suggested that V2a interneurons are acting on the commissural interneuron systems controlling left-right alternation Quinlan and Kiehn, 2007) especially at intermediate locomotor frequencies, provide inputs to segmental motor neurons, and are not directly involved in rhythm generation (Crone et al, 2008(Crone et al, , 2009). However, the previous studies did not provide any information about the relationship of the activity of the Chx10 population during locomotor-like activity.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…A consecutive study confirmed these findings and showed that the disruption in left-right alternation was most pronounced at intermediate locomotor frequencies (Crone et al, 2009). Together, these studies therefore suggested that V2a interneurons are acting on the commissural interneuron systems controlling left-right alternation Quinlan and Kiehn, 2007) especially at intermediate locomotor frequencies, provide inputs to segmental motor neurons, and are not directly involved in rhythm generation (Crone et al, 2008(Crone et al, , 2009). However, the previous studies did not provide any information about the relationship of the activity of the Chx10 population during locomotor-like activity.…”
Section: Introductionmentioning
confidence: 66%
“…The Chx10 neurons are exclusively glutamatergic and project ipsilaterally (Al-Mosawie et al, 2007;Lundfald et al, 2007). Recently, we have shown that left-right alternation is disrupted in transgenic mice in which Chx10 neurons have been selectively ablated by diphtheria toxin A, whereas alternation between flexors and extensors on the same side remains intact (Crone et al, 2008). In the absence of V2a interneurons, locomotor activity also showed an increase in the variability of burst frequency and amplitude (Crone et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, light-induced locomotor-like activity has a higher burst frequency than seen with other methods (up to 2.7 Hz), is well tuned, and is instantaneously turned on with the appropriate pattern. Drug-induced locomotor-like activity is readily evoked and can be maintained for hours, permitting long timespan analysis in wild type as well as mutant and lesioned animals (45)(46)(47)(48)(49)(50). Although the activity most likely uses the same networks as under in vivo conditions, an obvious drawback is that the drugs act upon every neuron in the spinal cord, not all of which are necessarily components of the locomotor network.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that V2a interneurons in the ventral spinal cord run ipsilaterally, display rhythmicity, and provide excitatory input to CPG interneurons and propriospinal networks [10][11][12]. Genetic ablation of V2a in mice leads to the loss of left-right coordination during locomotor activities [11], whereas targeted ablation of cervical V2a subpopulations leads to deficits in reaching movements [10]. Cells homologous to V2a interneurons in zebrafish have been shown to span greater than two spinal cord segments and synapse onto motoneurons [13].…”
Section: Introductionmentioning
confidence: 99%